Optimization of molecular biology protocols commonly used in research labs - Mina Tigasi, Vicky Patricia (2026)
In research laboratories all around the world, traditional (kit-free) protocols for DNA extraction, universal settings for PCR amplification and protocols for bacterial transfor mation are commonly employed. Interestingly, there are many widespread practices and protocols that have been unaltered for decades, but could be subject to improvements. As an example, all the scientific literature coincides in denaturation temperatures of around 95°C for the PCR reactions. Also, there is the belief that the DNA yield increases in the traditional DNA extraction process when using absolute ethanol if the sample is kept in the cold for half an hour. Finally, most molecular biology scientists performing bacterial transformations believe that the electroporation method yields more CFUs per microgram of DNA than the chemical (CaCl2) method. In this work we have tested some of the con ditions related to these three molecular biology processes related to the use of DNA and found that it is possible to i) perform PCR reactions at lower denaturation temperatures than 95°C; ii) prove that the temperature does not play a role during the traditional DNA extraction proces; iii) the chemical method can produce more CFUs/µg than the electro poration method, when using E. coli DH5α cells optimized for the chemical method.